2007
DOI: 10.1021/jp068549t
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale Coarse-Graining and Structural Correlations:  Connections to Liquid-State Theory

Abstract: (2005)]. If no approximations are made, the MS-CG method yields a many-body multi-dimensional potential of mean force describing the interactions between CG sites. However, numerical applications of the MS-CG method typically employ a set of pair potentials to describe non-bonded interactions. The analogy between coarse-graining and the inverse problem of liquid state theory clarifies the general significance of three-particle correlations for the development of such CG pair potentials. It is demonstrated that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
283
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 198 publications
(287 citation statements)
references
References 49 publications
4
283
0
Order By: Relevance
“…28,29,[45][46][47][48][49][50][51]63 This suggests that nonbonded interactions between CG sites are often well represented, at least to a good first approximation, as pairwise additive. A recent analysis 30 has also demonstrated that the MS-CG equations for these pair potentials are related to well-known exact kinetic equations for the liquid state 67 and systematically incorporate critical three-body correlations present in the underlying atomistic model, which may be a key feature in the previous successes of the MS-CG method.…”
Section: Discussionmentioning
confidence: 99%
“…28,29,[45][46][47][48][49][50][51]63 This suggests that nonbonded interactions between CG sites are often well represented, at least to a good first approximation, as pairwise additive. A recent analysis 30 has also demonstrated that the MS-CG equations for these pair potentials are related to well-known exact kinetic equations for the liquid state 67 and systematically incorporate critical three-body correlations present in the underlying atomistic model, which may be a key feature in the previous successes of the MS-CG method.…”
Section: Discussionmentioning
confidence: 99%
“…There are two methods belonging to the force-based methods: the force-matching method [168] and the multiscale coarse-graining method [169,170]. The latter was validated through rigorous statistical thermodynamic formulations by Noid et al [171][172][173]. Rühle et al [174] implemented the IBI, IMC and force-matching methods into a toolkit and compared them by coarse-graining water molecules, liquid methanol, liquid propane and a single molecule of hexane.…”
Section: Iterative Boltzmann Inversion Methodsmentioning
confidence: 99%
“…[17]. Furthermore, there is recent interest in developing coarse-graining methods based on this theory, see for example [29,33,34].…”
Section: Introductionmentioning
confidence: 99%